The prevalence and years lived with disability of asthma in children under 5 years old in Sichuan Southwest China, 1990–2019: A cross-sectional study - Luo, Yu; Bao, Li; Wang, Mu; Guo, Hui (Frontiers in Pediatrics, 2022)
Objectives To analyze the prevalence and Years Lived with Disability of Asthma in children under 5 years old and the time trends in Sichuan Southwest China from 1990-2019. Methods Based on the results of the Global Burden of Disease Study 2019 (GBD2019), we present the time trend, sex specific prevalence, Years Lived with Disability (YLDs) and deaths due to asthma under 5 years old in Sichuan and compared them with national indicators in the same period. Results The number of children under 5 years old with asthma decreased overall from 1990 to 2007 and increased overall from 2008 to 2019. The time trend of prevalence rate was similar. In 2019, over 111 thousands children under 5 years old suffered from asthma, the prevalence rate was 2,584 per 100 thousand, YLDs was 4.5 thousands, and YLDs rate was 105 per 100 thousand in Sichuan. Compared with 1990, the number of patients decreased by 48.6%, the prevalence increased by 9.4%, the YLDs decreased by 48.9%, and the YLDs rate increased by 9.7% in 2019. The increase in the prevalence and YLDs rate of asthma children in Sichuan was higher than the national overall, but the number of asthma deaths and deaths rate in Sichuan and the whole nation all decreased. Conclusions The results in Sichuan Southwest China show the prevalence and YLDs of asthma children under 5 years old increased over the past 30 years, and were higher than the overall increase in China. Male children are the key population of increasing asthma disease burden and deserves more attention. More targeted prevention and control measures are still needed to reduce the incidence of asthma.